Beautiful terrible ruins : Detroit and the anxiety of decline - Apel, Dora, 1952- (Rutgers University Press, 2015)
Detroit is the epicenter of an explosive growth in images of urban decay. In Beautiful Terrible Ruins, art historian Dora Apel explores a wide array of these images of ruin, ranging from photography, advertising, and television, to documentaries, video games, and zombie and disaster films. The author shows how, through the aesthetic distancing of representation, the beauty and fascination of these images helps us to cope with the overarching anxieties of our time.